Making intelligence smarter. - Zorpette, G.E (IEEE spectrum)
After a decade of drift in which intelligence agencies seemed to be casting about for a mission worthy of their big budgets, they have at last found one. But in adapting to global terrorism inspired by Islamist fundamentalism, those agencies will be forced to reassess many long-held customs and beliefs. They will have to find new human assets, including spies and analysts, and new ways to use their technical infrastructures, while cooperating more actively with domestic partners and with foreign intelligence services of every stripe. Agencies must find a new balance between electronic eavesdropping and spies on the ground to counter global terrorism